SELF-MONITORING DAN IMPULSIVE BUYING PRODUK KOSMETIK DI KALANGAN MAHASISWI: STUDI KORELASI - Milazia Putri; Intan Dewi Kumala; Risana Rachmatan; Arum Sulistyani (Journal of Community Mental Health and Public Policy)
ABSTRACT Background: Female students as late teens are individuals who have the tendency to do impulsive buying or spontaneous buying. In making purchases, female students are easily influenced which made them buy items that are popular in their social environment. This is related to high self-monitoring, mostly due to the idea of always wanting to display a positive image of themselves, and to behave in accordance with the information received from their environment. Purpose: To determine the relationship between self-monitoring and impulsive buying of cosmetic products among female college students of Universitas Syiah Kuala. Methods: This study used a quantitative approach involving 337 female college students aged 18-22 years, who were selected through the unrestricted self-selected survey technique. Data was collected using a revised version of self-monitoring scale and impulsive buying tendency scale. Pearson correlation was used to test the association. Results: The results showed that c. There was a positive and significant relationship between self-monitoring and impulsive buying of cosmetic products among female college students (r = 0.568; p = 0.000), meaning that the higher the self-monitor, the greater the impulsive buying, and vice versa. The coefficient of determination was 0.322 which indicates that self-monitoring contributes 32.2% to impulsive buying. Conclusion: Self-monitoring and impulsive buying of cosmetic products were both high among female college students. Self monitoring is positively associated with impulsive buying among these group.